Predictors of self-care behaviour using health belief model among type 2 diabetes mellitus patients in a district of Penang, Malaysia - Kang, Chia Yee (2017)
Background: The prevalence of diabetes mellitus among Malaysian aged ≥ 18 years increasing from 11.6% in 2006 to 17.5% in 2015. The diabetes prevalence in Penang state was 18.1% in 2015. Only 21% of audited type 2 diabetes mellitus (T2DM) patients in Penang achieved hemoglobin A1c < 6.5% in 2012. Positive self–care behaviour leads to good glycaemic control and reduce risk of diabetes complications.